PEDAGOGICAL CONDITIONS OF EFFECTIVE FORMATION OF SPIRITUALITY SENIOR STUDENTS IN PROCESS INTERPRETATIONS OF WORKS (Pedagogy of Higher and Secondary Education, 2022)
The article is devoted to the questions of forming spirituality of senior pupils by means of interprétation of artistic literature, especially pedagogical conditions, which will contrihute effective performing of described influence.